A MEASUREMENT OF D-MESON PRODUCTION IN Z(0) HADRONIC DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Algeri, A; Allen, P; Almehed, A; Alvsvaag, S; Amaldi, U; et al. (1993)
A study of the fragmentation properties of charm and bottom quarks into D mesons is presented. From 263 700 Z0 hadronic decays collected in 1991 with the DELPHI detector at the LEP collider, D0, D+ and D*+ are reconstructed in the modes K-π+, K-π+K+ and D0π+ followed by D0→K-π+, respectively. The fractional decay widths Mathematical expression are determined, and first results are presented for the production of D mesons from Mathematical expression and Mathematical expression events separately. The average energy fraction of D*± in charm quark fragmentation is found to be 〈XE(D*)〉c=0.487± 0.015 (stat)±0.005 (sys.). Assuming that the fraction of Ds and charm-baryons produced at LEP is similar to that around 10 GeV, the Z0 partial width into charm quark pairs is determined to be Γc/Γh=0.187±0.031 (stat)±0.023 (sys). The probability for a b quark to fragment into Mathematical expression or b-baryons is inferred to be 0.268±0.094 (stat)±0.100 (sys) from the measured probability that it fragments into a Mathematical expression or B-. © 1993 Springer-Verlag.